Robot assisted hysterectomy - its benefits and advantages over other routes of hysterectomies: a retrospective cohort study - Dadhich, C. P.; Mehta, Nidhi; Dadhich, Tripti; Sharma, Surmil; Mangal, Shweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Minimally invasive hysterectomy has become the preferred approach for benign gynecological conditions. Robot-assisted laparoscopic hysterectomy (RALH) has been introduced to overcome certain technical limitations of conventional laparoscopy. Methods: This retrospective cohort study included 165 women undergoing hysterectomy for benign gynecological indications at a tertiary care center between November 2023 and February 2024. Patients underwent RALH, total laparoscopic hysterectomy (TLH), total abdominal hysterectomy (TAH) or vaginal hysterectomy (VH). Perioperative outcomes including operative time, estimated blood loss (EBL), length of hospital stay (LOS), postoperative pain scores (VAS) and complications were compared. Results: Of the 165 cases, 43 underwent RALH, 64 TLH, 26 TAH and 32 VH. Baseline demographic parameters were comparable across groups. RALH was associated with significantly lower mean blood loss (8.49±5.51 ml), shorter hospital stay (1.3±0.4 days) and lower postoperative VAS scores compared to other routes (p<0.001). No conversions to laparotomy were required. Secondary hemorrhage was least frequent in the RALH group. Conclusions: Robot-assisted hysterectomy demonstrates favorable perioperative outcomes in selected patients with benign gynecological conditions. While clinical differences were statistically significant, their impact should be interpreted in the context of patient selection and resource availability.